Brain Pathways: New Approaches to Structure-Function Localization. - Martin, Joseph B.; Samuels, Martin (Psychiatric Times, 2016)
The article presents information on the concept of structure-function localization of brain functions of humans. Topics include the Human Connectome Project of Matthew Glasser and David Van Essen of Washington University in St. Louis, Missouri, the neurological method of the localization theory, and awareness of precise regional circuit localization via deep brain stimulation (DBS) and transcranial magnetic stimulation (TMS).